The consequences of differential origin licensing dynamics in distinct chromatin environments. Issue 17 (26th January 2022) - Mei, Liu; Kedziora, Katarzyna M; Song, Eun-Ah; Purvis, Jeremy E; Cook, Jeanette Gowen
Abstract: Eukaryotic chromosomes contain regions of varying accessibility, yet DNA replication factors must access all regions. The first replication step is loading MCM complexes to license replication origins during the G1 cell cycle phase. It is not yet known how mammalian MCM complexes are adequately distributed to both accessible euchromatin regions and less accessible heterochromatin regions. To address this question, we combined time-lapse live-cell imaging with immunofluorescence imaging of single human cells to quantify the relative rates of MCM loading in euchromatin and heterochromatin throughout G1. We report here that MCM loading in euchromatin is faster than that in heterochromatin in early G1, but surprisingly, heterochromatin loading accelerates relative to euchromatin loading in middle and late G1. This differential acceleration allows both chromatin types to begin S phase with similar concentrations of loaded MCM. The different loading dynamics require ORCA-dependent differences in origin recognition complex distribution. A consequence of heterochromatin licensing dynamics is that cells experiencing a truncated G1 phase from premature cyclin E expression enter S phase with underlicensed heterochromatin, and DNA damage accumulates preferentially in heterochromatin in the subsequent S/G2 phase. Thus, G1 length is critical for sufficient MCM loading, particularly in heterochromatin, to ensure complete genome duplication and to maintain genome stability. Lay Summary: In this study the authors have, for the first time, quantified DNA replication origin licensing dynamics and distribution in single cells at subnuclear resolution. The cell cycle and DNA replication fields have long appreciated that origin licensing is both absolutely essential for replication and that licensing is strictly confined to G1 phase. The biochemical process of origin licensing- which is the DNA loading of MCM complexes- is known in considerable detail. What has never been explored in any system, is the dynamics of origin licensing itself. Here the authors define the dynamics of human MCM loading at different times within G1 in both euchromatin and heterochromatin, and explore the consequences of those dynamics for genome stability.